Phenomenology and artificial intelligence. The limits of subjectivity - Vargas Guillén, Germán (Estudios de Filosofía, 1999)
Having as a backbone what Husserl called Empiric Phenomenology, this paper aims at describing an Empiric Epistemology of Artificial Intelligence. In that sense, it is shown that once a phenomenological description o f the «essence» of a moral dilemma is translated into a logic strncture, it isfeasible to represent it in aplatfonn of software by means of an «inference engine». Such representation will lead to prove that in the solving of moral dilemmas, structures of self- cheating are used. Subjectivity is thus brought to the borders of representability and so its essence becomes suitable of reflexion.